The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1088/1748-605x/aaca5b
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic engineering of the cardiac tissue through processing, functionalization, and biological characterization of polyester urethanes

Abstract: Three-dimensional (3D) tissue models offer new tools in the study of diseases. In the case of the engineering of cardiac muscle, a realistic goal would be the design of a scaffold able to replicate the tissue-specific architecture, mechanical properties, and chemical composition, so that it recapitulates the main functions of the tissue. This work is focused on the design and preliminary biological validation of an innovative polyester urethane (PUR) scaffold mimicking cardiac tissue properties. The porous sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 72 publications
(93 reference statements)
0
19
0
Order By: Relevance
“…Interestingly, the coating of n-HA on the surface of electrospun PLLA nanofibers was also found effective for bone formation within 10 weeks after subcutaneous implantation, which was not the case when using plasma-activated PLLA scaffolds. Consequently, the authors suggested that the n-HA directly coated on the surface of nanofibers can induce ectopic bone formation in vivo in the absence of exogenous inductive agents or cells [297].…”
Section: Grafting Of Inorganic Particles On Plasma-activated Nanofibrmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the coating of n-HA on the surface of electrospun PLLA nanofibers was also found effective for bone formation within 10 weeks after subcutaneous implantation, which was not the case when using plasma-activated PLLA scaffolds. Consequently, the authors suggested that the n-HA directly coated on the surface of nanofibers can induce ectopic bone formation in vivo in the absence of exogenous inductive agents or cells [297].…”
Section: Grafting Of Inorganic Particles On Plasma-activated Nanofibrmentioning
confidence: 99%
“…Besides plasma activation, which is by far the most commonly applied plasma-based method to nanofibrous TE scaffolds, some authors have also conducted plasma polymerization experiments on electrospun nanofibers [297][298][299][300][301]. In this case, monomer molecules in the vapor phase (typically carried by an inert gas flow) are introduced in the active plasma region.…”
Section: Plasma Polymerizationmentioning
confidence: 99%
“…The second step involves biomaterial synthesis, which entails the development of novel biomaterials that can be used to simulate mammalian extracellular matrix (ECM). A large number of biomaterials have been used in the field, to include collagen type I, fibrin, gelatin, alginate, and chitosan, to name a few (18). The third step involves coupling contractile CMs with novel biomaterials to generate functional ventricles, in other words, develop novel fabrication methods to bioengineer functional ventricles.…”
Section: Process To Bioengineer Ventriclesmentioning
confidence: 99%
“…The notion to bioengineer cardiac patches is easy to understand as the potential applications to repair infarcted myocardium tissue are now well-established (18,19). Similarly, the utility of vascular grafts, aortic and mitral valves, and whole hearts for potential therapeutic purposes is evident and well-described (19).…”
Section: The Need For Bioengineered Ventriclesmentioning
confidence: 99%
“…In addition to traditional 2-dimensional (2D) in vitro systems, three-dimensional (3D) tissue models have also offered new tools in the study of cardiovascular disease recently [15]. In response to 3D conditions, the activation of ERK1/2 was observed during cardiomyogenesis, and the phosphorylation of ERK1/2 was higher compared to cells on 2D films, which provides insight into ERK1/2 pathways driving heart development [16,17]. With regard to the whole organ phenomenon in a dynamically changing neuroendocrine environment under cardiac hypertrophy and heart failure, culture-based or tissue-engineering approaches have only provided some basic physiological parameters within a largely 2D or 3D environment [18].…”
Section: Introductionmentioning
confidence: 99%